WAYS TO ACTIVATE STUDENT INDEPENDENT EDUCATION - Hayitova Shakhnoza Daniyarovna (Journals Park Publishing, 2022)
The content, ways of organizing students' independent learning, the types and objectives of independent learning are described in this article.It also reports that the levels and criteria of independent learning activities, the stages of the implementation of independent learning, the ways of developing the skills and competence of working independently,as well as the degrees of students' independent learning.
Keywords: criteria; knowledge; skills